How do you convert r=-3secthetar=3secθ into rectangular equations?

1 Answer
Jul 15, 2016

x = -3x=3

Explanation:

Knowing that x = r cos(theta)x=rcos(θ) and y = r sin(theta)y=rsin(θ), we can start off by rewriting our polar equation:

r = -3sec(theta) = -3 * (1)/(cos(theta))r=3sec(θ)=31cos(θ), so then

r = -3/cos(theta)r=3cos(θ)

Multiplying both sides by cos(theta)cos(θ) gives us

r cos(theta) = -3rcos(θ)=3

Substituting xx for r cos(theta)rcos(θ), since x = rcos(theta)x=rcos(θ) we get

x = -3x=3